Looking at the Japanese Automotive Industry through Indonesian Published Manga - Danendro Adi (Bina Nusantara University, 2017)
This article discussed manga and visual language that had been used on the Japanese fiction graphic narrative as a case study and graphic biography as a comparison. It implemented literature study approach on illustration, specifically, sequential art literature to obtain data as well as finding a theoretical framework to strengthen research results. The article began with a brief history of Japanese comics, then would be discussed the definition and common form of manga and how-to extent the media to convey the information and to identify the visual approach to narrating the information. It finds that modern manga has a potential to become an effective medium to narrate the Japanese culture, growth, and its technological advances that have gained global recognition.